Portfolio of Clinical Research in Adult Cardiovascular Disease as Reflected in ClinicalTrials.gov. Issue 5 (26th September 2013) - Alexander, Karen P.; Kong, David F.; Starr, Aijing Z.; Kramer, Judith; Chiswell, Karen; Tasneem, Asba; Califf, Robert M.
Abstract : Background: Cardiovascular medicine is widely regarded as a vanguard for evidence‐based drug and technology development. Our goal was to describe the cardiovascular clinical research portfolio from ClinicalTrials.gov. Methods and Results: We identified 40 970 clinical research studies registered between 2007 and 2010 in which patients received diagnostic, therapeutic, or other interventions per protocol. By annotating 18 491 descriptors from the National Library of Medicine's Medical Subject Heading thesaurus and 1220 free‐text terms to select those relevant to cardiovascular disease, we identified studies that related to the diagnosis, treatment, or prevention of diseases of the heart and peripheral arteries in adults (n=2325 [66%] included from review of 3503 potential studies). The study intervention involved a drug in 44.6%, a device or procedure in 39.3%, behavioral intervention in 8.1%, and biological or genetic interventions in 3.0% of the trials. More than half of the trials were postmarket approval (phase 4, 25.6%) or not part of drug development (no phase, 34.5%). Nearly half of all studies (46.3%) anticipated enrolling 100 patients or fewer. The majority of studies assessed biomarkers or surrogate outcomes, with just 31.8% reporting a clinical event as a primary outcome. Conclusions: Cardiovascular studies registered on ClinicalTrials.gov span a range of study designs. Data have limited verification or standardization and require manual processes to describe and categorize studies. The preponderance of small and late‐phase studies raises questions regarding the strength of evidence likely to be generated by the current portfolio and the potential efficiency to be gained by more research consolidation.